2020
DOI: 10.1101/2020.01.30.927616
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning reveals heterogeneous responses to FAK, Rac, Rho, and Cdc42 inhibition on vascular smooth muscle cell spheroid formation and morphology

Abstract: Hyper proliferation of vascular smooth muscle cells (VSMCs) contributes to neointima formation in atherosclerosis and the response to vascular injury. Understanding how to control VSMC proliferation would advance the effort to treat vascular disease. Drug responses are often different among patients with the same vascular disease condition, making it difficult to cater patientspecific treatments (existence of heterogeneity). Thus, we examined variations in response to drug treatments using VSMC spheroids that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the focal adhesion kinase (FAK) has been reported to control the proliferation of VSMCs through N-Cadherin and is significant to cell adhesion. Then, Vaidyanathan et al created a spheroid VSMC model to study the focal adhesion FAK gene and the regulation of its downstream genes, such as Rac, Rho, and Cdc42, aiming to identify potential pathways to treat neointima formation (153). By quantifying the expression of Rac and Rho in the VSMC spheroids, the authors found that FAK-Rac-N-cadherin or FAK-Rho-N-cadherin are necessary for VSMC spheroid formation, which might be considered a future target for treating atherosclerosis-related neointima formation (153).…”
Section: In Vitro 3d Spheroidsmentioning
confidence: 99%
“…Furthermore, the focal adhesion kinase (FAK) has been reported to control the proliferation of VSMCs through N-Cadherin and is significant to cell adhesion. Then, Vaidyanathan et al created a spheroid VSMC model to study the focal adhesion FAK gene and the regulation of its downstream genes, such as Rac, Rho, and Cdc42, aiming to identify potential pathways to treat neointima formation (153). By quantifying the expression of Rac and Rho in the VSMC spheroids, the authors found that FAK-Rac-N-cadherin or FAK-Rho-N-cadherin are necessary for VSMC spheroid formation, which might be considered a future target for treating atherosclerosis-related neointima formation (153).…”
Section: In Vitro 3d Spheroidsmentioning
confidence: 99%